2022
DOI: 10.1186/s12939-022-01778-2
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge of COVID-19 and the impact on indigents’ access to healthcare in Burkina Faso

Abstract: Background COVID-19 constitutes a global health emergency of unprecedented proportions. Preventive measures, however, have run up against certain difficulties in low and middle-income countries. This is the case in socially and geographically marginalized communities, which are excluded from information about preventive measures. This study contains a dual objective, i) to assess knowledge of COVID-19 and the preventive measures associated with it concerning indigents in the villages of Dieboug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The current results also demonstrated the importance of accessible information as a significant predictor of LTC facilities' adherence to COVID‐19 prevention and control recommendations. Poor access to information about COVID‐19 prevention and control has been reported particularly in low‐ and middle‐income countries, as well as the socially and geographically marginalized communities (Bonnet et al, 2022; McHunu et al, 2022; Wang et al, 2020). Poor access to information was also associated with experiencing more COVID‐19 stigma (Adhikari et al, 2022) and a lack of adherence to measures to combat the pandemic (Lowe et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The current results also demonstrated the importance of accessible information as a significant predictor of LTC facilities' adherence to COVID‐19 prevention and control recommendations. Poor access to information about COVID‐19 prevention and control has been reported particularly in low‐ and middle‐income countries, as well as the socially and geographically marginalized communities (Bonnet et al, 2022; McHunu et al, 2022; Wang et al, 2020). Poor access to information was also associated with experiencing more COVID‐19 stigma (Adhikari et al, 2022) and a lack of adherence to measures to combat the pandemic (Lowe et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in the first sentence of the Methods-section, “(GODIN)” should have read “[30]”.…”
mentioning
confidence: 99%